Surface Texturing of TiO2 Film by Mist Deposition of TiO2 Nanoparticles - Qin, Gang; Watanabe, Akira (Nano-Micro Letters, 2013)
Unique and various microstructures of titanium oxide (TiO2) film including macroporous structure, chromatic veins and rings, have been easily fabricated by mist deposition method on silicon substrate with mild preparation conditions. Rutile phase TiO2 nanoparticles were directly used as starting material to prepare film and led to a simple preparation process. It was found that several different microstructures existed in the sample and changed with the varied positions from the center to the edge of the film when the concentration of the TiO2 suspension is 0.06 mol/l, the deposition time is 30 min, the flow rate is 1 l/min and the temperature is 150°C. The surface texturing shows apparent distinction as the concentration of the TiO2 suspension decreased to 0.03 mol/l and 0.01 mol/l.